APPLICATION OF THE ECONOMIC ORDER QUANTITY (EOQ) METHOD IN CONTROLLING MORINGA LEAF RAW MATERIALS (Case Study: CV. Atlantic North Aceh District) - Nurbaiti Nurbaiti (AGRIBUSINESS JOURNAL, 2023)
This research was conducted with the aim of knowing how many orders for raw materials for Moringa leaves in order to get optimal costs using the Economic Order Quantity (EOQ) method that occurred at CV. Atlantic in Tanjung Ara Village, Tanah Jambo Aye District, North Aceh District. Primary data was obtained by observation, interviews using direct questionnaires with respondents. Secondary data was obtained through journals, books and company records for one year (January-December 2022). In this study has one sample, namely the owner or director of CV. Atlantic. The determination of the sample used in the study used the case study method where the number of samples taken only came from internal informants, namely the Director and Deputy Director of CV.Atlantic. The data analysis method used in this study is the Economic Order Quantity (EOQ), Safety Stock (SS) and Re Order Point (ROP) methods. The research results obtained on the EOQ method were as much as 32.16 kg with a frequency of purchasing moringa leaf raw materials 16 times in one year. The total cost of raw material inventory based on CV. Atlantic which is Rp 7,378,764.00, while based on calculations using the EOQ method the total cost of raw material inventory for moringa leaves is Rp 580,731.25 so using the EOQ method CV. Atlantic can save as much cost Rp 6,789,032.75. Safety Stock based on the EOQ method of 2.35 kg / month of moringa leaf raw material. Re Order Point based on the EOQ method of 3.78 kg.Keywords: Inventory Control, Raw Materials, EOQ